Determinants of Firm's Value through Capital Structure, Financial Performance, and Company Growth - Rahmah Alwan; Asep Risman (Universitas Mercu Buana, 2023)
This study aims to determine the influence of capital structure represented by Debt to Equity Ratio (DER), the financial performance represented by Return on Asset (ROA), and the growth of companies represented by Total Asset Growth (TAG) on the value of companies in the agricultural industry sector listed on the Indonesia Stock Exchange. The population used in this study was as many as 25 companies. The sampling method used is the purposive sampling method, so that 9 companies with 5 years of observation (2016-2020) were obtained so that 45 observational data were produced. The research data was obtained from the Indonesia Stock Exchange website. The data analysis techniques used are descriptive statistics and panel data. The results of the study partially showed that the capital structure (Debt to Equity Ratio) had a negative effect, financial performance (Return on Assets) had a positive effect, and company growth (Total Asset Growth) did not affect the value of the company.